2015
DOI: 10.1152/ajpregu.00079.2015
|View full text |Cite
|
Sign up to set email alerts
|

Forearm cutaneous vascular and sudomotor responses to whole body passive heat stress in young smokers

Abstract: 2 /min/°C ⌬Tb, respectively, P ϭ 0.81; CVC: 82.5 Ϯ 46.2 vs. 58.9 Ϯ 23.3 ⌬%max/°C ⌬Tb, respectively; P ϭ 0.19). However, the plateau in LSR during whole body heating was higher in N-SMK vs. SMK (1.00 Ϯ 0.13 vs. 0.79 Ϯ 0.26 mg·cm Ϫ2 ·min Ϫ1 ; P ϭ 0.03), which was likely a result of higher SGO (8.94 Ϯ 3.99 vs. 5.94 Ϯ 3.49 g·gland Ϫ1 ·min Ϫ1 , respectively; P ϭ 0.08) and not number of SGA (104 Ϯ 7 vs. 121 Ϯ 9 glands/cm 2 , respectively; P ϭ 0.58). During whole body passive heat stress, smokers had an earlier onset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Activation of PAR2 has also been shown to counteract the endothelin-1-induced vasoconstrictor effect (Roviezzo et al 2016). Further research is warranted to evaluate whether microvascular dysfunction associated with ageing (Holowatz et al 2006), obesity (Patik et al 2016), cigarette smoking (Fujii et al 2013;Moyen et al 2015), type 2 diabetes (Wick et al 2006), polycystic ovary syndrome (Wenner et al 2013) and other chronic health conditions is improved by PAR2 activation. In line with this idea, we show that PAR2 activation can induce a cutaneous vasodilatory effect in part attributable to NO, an important cardioprotective molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of PAR2 has also been shown to counteract the endothelin-1-induced vasoconstrictor effect (Roviezzo et al 2016). Further research is warranted to evaluate whether microvascular dysfunction associated with ageing (Holowatz et al 2006), obesity (Patik et al 2016), cigarette smoking (Fujii et al 2013;Moyen et al 2015), type 2 diabetes (Wick et al 2006), polycystic ovary syndrome (Wenner et al 2013) and other chronic health conditions is improved by PAR2 activation. In line with this idea, we show that PAR2 activation can induce a cutaneous vasodilatory effect in part attributable to NO, an important cardioprotective molecule.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on more than 700 healthy volunteers showed serum CEA levels in smokers can rise to double of that in non‐smokers, the upper limit of normal range . Chronic smoking also affects the earlier onset and lower peak of sweating during passive heat stress . However, the effect is limited and not enough to be responsible for the pathogenesis of hypohidrosis/anhidorosis.…”
Section: Discussionmentioning
confidence: 99%
“…10 Chronic smoking also affects the earlier onset and lower peak of sweating during passive heat stress. 11 However, the effect is limited and not enough to be responsible for the pathogenesis of hypohidrosis/ Serum CEA in hypohidrosis and anhidrosis anhidorosis. While there were regular smokers among the subjects in this study, smoking alone did not explain the increased serum CEA level in the results ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, since cigarette smoking can increase nicotine levels in the body, our result may provide some insights into the underlying mechanisms by which cigarette smoking modulates cutaneous vasodilation and sweating during heat exposure (Moyen et al 2015) as well as microvascular function Fujii et al 2014a).…”
Section: Introductionmentioning
confidence: 86%